Optimizing age at first freezing in relation to fertility of Murrah breeding bulls - MIR, M A; CHAKRAVARTY, A K; NAHA, B C; JAMUNA, V; PATIL, C S; SINGH, A P (The Indian Journal of Animal Sciences, 2015)
The optimization of age at first freezing in Murrah breeding bulls has been studied which will help in early selection of bulls for improving the reproductive performance in the herd. The data pertaining to age at first freezing (AAFF), conception rate based on first AI (CRFAI), overall conception rate (OCR) and birth weight (B.WT) of 57 Murrah bulls during 1993 to 2014 belonging to 14 sets of Network Project on Buffalo Improvement at ICAR-National Dairy Research Institute, Karnal, Haryana were adjusted against environmental influence and subsequently analyzed. Simple and multiple regression models were developed for prediction of CRFAI and OCR of Murrah breeding bulls. By judging of three developed models (I to III) it was observed that Model III having age at first freezing and birth weight fulfill the accuracy of model, i.e. high coefficient of determination, low mean sum of square, due to error (MSSe), low conceptual predictive value (Cp value) and low Bayesian information criterion (BIC). The results revealed that optimum age at first freezing of Murrah bulls should be 2.5-3.0 years for 4.98% better conception rate based on first AI and 3.92% better overall conception rate in comparison to Murrah bulls with more than 3.5 years of age.